Thermophysical and mechanical properties of fiber‐reinforced composite material subjected to high temperatures - Vejmelková, Eva; Konvalinka, Petr; Padevět, Pavel; Černý, Robert (Journal of Civil Engineering and Management, 2010)
The bulk density, open porosity, matrix density, tensile strength, bending strength, thermal diffusivity, specific heat capacity, thermal conductivity and linear thermal expansion coefficient of high‐density glass fiber reinforced cement composite are determined as functions of temperature up to 1000 °C. The basic physical parameters and mechanical parameters are found to exhibit the most important changes between the reference state and 600 °C pre‐heating where the increase of porosity is as high as 40% and both the tensile strength and bending strength decrease to about one third of their original values. The measured dependences of thermal diffusivity and thermal conductivity on temperature indicate that the heat transfer in the studied material is accelerated once temperature achieves 500–600 °C but the change in heat storage expressed by the specific heat capacity is less important. The linear thermal expansion coefficient is not found to be affected by high temperatures in a negative way; it is either lower or comparable to its low‐temperature values. First Published Online: 10 Feb 2011